Performance of indigenous chicken under intensive rearing with various litter materials - M. Sulistyoningsih; Dwi Sunarti; Ejeng Suprijatna; I. Isroli (Chemical Engineering Diponegoro University, 2013)
The purpose of the research was to obtain information regarding the performance of indigenous chicken under intensive rearing. The performance criteria were the increasing body abdominal weight, fat, rectal temperature, and the indigenous chicken’s mortality within the 5-week starter phase treatment. Research was conducted using 108 Day Old Chick (DOC). Data variance was analysed based on the split plot design (3 types of cage litter materials, 5 weeks of data collection, and 4 replications) for weight gain and abdominal fat parameters, and completely randomized design in time for rectal temperature. The result indicated a significant effect of different litter materials towards weight gain (P <0.01), the highest body weight was found on chicken treated with rice straw litter; there was no effect of litter material on abdominal fat percentage; there was a significant effect (P < 0.01) of age towards rectal temperature; and there were no interactions between litter material with age, on body weight gain, abdominal fat, and rectal temperature. Chickens under intensive rearing in rice straw floored cages were proven to have a mortality rate reduced by 3.7% in the starter phase.doi: http://dx.doi.org/10.12777/ijse.4.2.2013.52-56 [How to cite this article: Sulistyoningsih, M., Sunarti, D., Suprijatna, E., & Isroli, I. (2013). Performance of indigenous chicken under intensive rearing with various litter materials. INTERNATIONAL JOURNAL OF SCIENCE AND ENGINEERING, 4(2), 52-56; doi: http://dx.doi.org/10.12777/ijse.4.2.2013.52-56